2002
DOI: 10.1113/jphysiol.2002.032151
|View full text |Cite
|
Sign up to set email alerts
|

Gating properties of girk channels activated by gαo‐ and GαiCoupled Muscarinic m2 Receptors in Xenopus Oocytes: The Role of Receptor Precoupling in RGS Modulation

Abstract: ‘Regulators of G protein Signalling’ (RGSs) accelerate the activation and deactivation kinetics of G protein‐gated inwardly rectifying K+ (GIRK) channels. In an apparent paradox, RGSs do not reduce steady‐state GIRK current amplitudes as expected from the accelerated rate of deactivation when reconstituted in Xenopus oocytes. We present evidence here that this kinetic anomaly is dependent on the degree of G protein‐coupled receptor (GPCR) precoupling, which varies with different Gαi/o‐RGS complexes. The gating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
75
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 74 publications
(111 reference statements)
8
75
0
Order By: Relevance
“…To yield reproducible data, we optimized the assay system, primarily in experiments with expressed M2 receptors. In previous studies, RGS proteins were shown to accelerate the deactivation kinetics of GIRK currents via G␣-mediated GTP hydrolysis, while also increasing the activation rates of GIRK currents (18)(19)(20). Coexpression of RGS4 did indeed result in faster activation and deactivation kinetics in I K,Agonist traces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To yield reproducible data, we optimized the assay system, primarily in experiments with expressed M2 receptors. In previous studies, RGS proteins were shown to accelerate the deactivation kinetics of GIRK currents via G␣-mediated GTP hydrolysis, while also increasing the activation rates of GIRK currents (18)(19)(20). Coexpression of RGS4 did indeed result in faster activation and deactivation kinetics in I K,Agonist traces.…”
Section: Resultsmentioning
confidence: 99%
“…1 illustrates the basic protocol. The basal K ϩ current (I K,Basal ) results primarily from the presence of free intracellular G␤␥ (17,18). The agonist-induced current (I K,Agonist ) is measured relative to the basal K ϩ current.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the G protein activation steps, signal termination with GTP hydrolysis by the G␣ subunit and G␤␥ reassociation also impacts the kinetics and amplitude of agonist-activated GIRK currents. The ternary complex consisting of agonist, GPCR, and G protein influences the time course of agonist-elicited GIRK channel currents (3), supporting the notion that isoform composition of different GPCR-G␣ i/o ␤␥ protein-RGS protein-GIRK channel signaling complexes have different kinetic properties that affect their functional output (4). We recently reported notable differences in the gating properties of GIRK channels activated by muscarinic m2 receptors coupled specifically to PTX-insensitive G␣ i isoforms (G␣ i1 , G␣ i2 , or G␣ i3 ) versus G␣ o isoforms (G␣ oA or G␣ oB ) in the Xenopus oocyte system (4).…”
mentioning
confidence: 76%
“…The ternary complex consisting of agonist, GPCR, and G protein influences the time course of agonist-elicited GIRK channel currents (3), supporting the notion that isoform composition of different GPCR-G␣ i/o ␤␥ protein-RGS protein-GIRK channel signaling complexes have different kinetic properties that affect their functional output (4). We recently reported notable differences in the gating properties of GIRK channels activated by muscarinic m2 receptors coupled specifically to PTX-insensitive G␣ i isoforms (G␣ i1 , G␣ i2 , or G␣ i3 ) versus G␣ o isoforms (G␣ oA or G␣ oB ) in the Xenopus oocyte system (4). The ACh-elicited activation time course for G␣ o -coupled GIRK currents was ϳ3-fold faster than for G␣ i -coupled GIRK currents, and G␣ o expression was significantly more effective than the G␣ i isoforms at reducing receptor-independent basal GIRK channel activity.…”
mentioning
confidence: 76%
See 1 more Smart Citation